Response of the muscles in the pelvic floor and the lower lateral abdominal wall during the Active Straight Leg Raise in women with and without pelvic girdle pain: An experimental study. (June 2016) - Sjödahl, Jenny; Gutke, Annelie; Ghaffari, Ghazaleh; Strömberg, Tomas; Öberg, Birgitta
Abstract: Background: The relationship between activation of the stabilizing muscles of the lumbopelvic region during the Active Straight Leg Raise test and pelvic girdle pain remains unknown. Therefore, the aim was to examine automatic contractions in relation to pre-activation in the muscles of the pelvic floor and the lower lateral abdominal wall during leg lifts, performed as the Active Straight Leg Raise test, in women with and without persistent postpartum pelvic girdle pain. Methods: Sixteen women with pelvic girdle pain and eleven pain-free women performed contralateral and ipsilateral leg lifts, while surface electromyographic activity was recorded from the pelvic floor and unilaterally from the lower lateral abdominal wall. As participants performed leg lifts onset time was calculated as the time from increased muscle activity to leg lift initiation. Findings: No significant differences were observed between the groups during the contralateral leg lift. During the subsequent ipsilateral leg lift, pre-activation in the pelvic floor muscles was observed in 36% of women with pelvic girdle pain and in 91% of pain-free women ( P  = 0.01). Compared to pain-free women, women with pelvic girdle pain also showed significantly later onset time in both the pelvic floor muscles ( P  = 0.01) and the muscles of the lower lateral abdominal wall ( P  < 0.01). Interpretation: We suggest that disturbed motor activation patterns influence women's ability to stabilize the pelvis during leg lifts. This could be linked to provocation of pain during repeated movements. Highlights: Muscle activity was measured during Active Straight Leg Raise test. Women with pelvic girdle pain had delayed pelvic floor muscle activation onset. Pelvic floor muscle pre-activation was lost during repeated Active Straight Leg Raise in women with pelvic girdle pain. Pelvic girdle pain might cause deteriorating pelvic stability during repeated tests.